2012
DOI: 10.1590/s0004-282x2012001000008
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative ultrasonography for presumed brain metastases: a case series study

Abstract: Brain metastases (BM) represent more than 50% of intracranial tumors in the adult population and have shown an increasing incidence over recent decades 1,2 . Around 170,000 patients per year are diagnosed with BM in the United States of America. In addition, 10% to 40% of oncologic patients develop BM in the course of the disease [1][2][3][4][5][6][7][8] . The factors associated with this increasing incidence include advances in neuroimaging techniques, easier access to health care systems, and increased survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
0
4
0
2
Order By: Relevance
“…IOUS facilitates total removal while protecting brain tissue and neurological symptoms improved in 80/ 98 (82%) patients and unchanged in 18 patients. Picarelli and colleagues [15], in their study on brain metastases surgery by IOUS, the total resection was achieved in 100%, and surgical morbidity and mortality were 3% and 5%, respectively. In my study, the total resection by IOUS was achieved in 86% of metastatic brain tumors.…”
Section: Discussionmentioning
confidence: 97%
“…IOUS facilitates total removal while protecting brain tissue and neurological symptoms improved in 80/ 98 (82%) patients and unchanged in 18 patients. Picarelli and colleagues [15], in their study on brain metastases surgery by IOUS, the total resection was achieved in 100%, and surgical morbidity and mortality were 3% and 5%, respectively. In my study, the total resection by IOUS was achieved in 86% of metastatic brain tumors.…”
Section: Discussionmentioning
confidence: 97%
“…One of the most important advantages of supporting the surgery is increasing the quality of living for our patients after the surgery. In addition to cranial metastases, in series where intraoperative USG is used for low and high-grade glial tumor imaging, they showed that the tumor tissue is clearly separated from the normal tissue in B mode imaging and use of intraoperative USG provided a surgical advantage in intracranial surgery [10][11][12].…”
Section: Journal Of Clinical and Analytical Medicinementioning
confidence: 99%
“…Brain metastases are more common than primary brain cancer, and there is debate over the best treatment protocol. 8 IOUS provides a means to help neurosurgeons more safely remove these metastatic lesions. Complete removal requires the capability to visualize all of the tumor borders and any residual cells during the surgery.…”
Section: Applications In Neurosurgerymentioning
confidence: 99%